A redescription of Metopa species (Amphipoda, Stenothoidae) based on the type material. 1. Zoological Museum, Copenhagen (ZMUC) - Tandberg, Anne Helene S.; Vader, Wim (Zootaxa, 2009)
This paper presents redescriptions of amphipods in the genus Metopa (Stenothoidae) in the type-collections of the Zoological Museum of Copenhagen. For Metopa clypeata and M. abyssalis we redescribe the type-specimens, for M. glacialis and M. groenlandica the redescriptions are based on new material and checked against the type-specimens. For all except M. abyssalis a combination of new line drawings and scanning electron microscope (SEM) pictures is provided, for M. abyssalis, line drawings only. A summary of the other species having earlier been designed to Metopa in the Copenhagen collections is given, with a list of their present taxonomic position.